Pathogenicity and histopathological observations of commercial broiler chicks experimentally infected with isolates of Eimeria tenella, E. acervulina and E. maxima - Zulpo, Dauton Luiz; Peretti, Jaidson; Ono, Leandro Mortean; Longhi, Elaine; Oliveira, Marcos R.; Guimarães, Ivens Gomes; Headley, Selwyn Arlington; Guimarães Junior, José da Silva; Garcia, João Luis (Semina: Ciências Agrárias, 2007)
Cooccidiosis is one of the most important causes of economic losses within the poultry industry. The objective of this study was to evaluate the pathogenicity of E. tenella, E. acervulina, and E. maxima strains in commercial broilers chicks. Thirty nine commercial one day old broiler chicks, unvaccinated against coccidiosis, were used during this experiment. At day 14, chickens of G1 (n=10), G2 (n=10) and G3 (n=10) were infected with 2 x 104 sporulated oocysts of E. tenella, E. acervulina, and E. maxima respectively; G4 (n=9) served as the uninfected control group. All birds were sacrificed with 21 day old (seven days after infection). The prepatent period (PPP) for G1 and G3 was seven days, however, E. acervulina (G2) had a PPP of five days. No statistical differences were observed when the average weight gain (G1=182.7±63.4; G2=145.2±51.0; G3=183.3±56.8; and G4=211.5±89.0, p>0.10) of the evaluated groups was compared. Average of lesion scores were determined G1 (1.3±0.48, scores 1(n=7) and 2(n=3)), G2 (0.4±0.52, scores 0(n=6), 1(n=4)), and G3 (1.1±0.99, scores 0(n=4), 1(n=1) and 2(n=5)). Chickens from the infected groups (G1, G2 and G4) did not demonstrate a lesion score above 2. The histopathological lesions induced by these strains were consistent with those described for infection by Eimeria spp.